iPhone photography - Hemmings, Mark (--For dummies., 2020)
Explains how to make meaningful and noticeable improvements in shooting technique using either the latest iPhone model or older versions to achieve professional-looking results, covering such topics as adjusting camera settings, selecting an editing app, and sharing and organizing images.